Impact of Delayed Cord Clamping on Neonatal Hemoglobin Levels in Term Infants: An Observational Study in Purwakarta Regency, Indonesia - Nurfitri, Tia (Archives of The Medicine and Case Reports, 2024)
Delayed cord clamping (DCC) is associated with improved iron stores and neurodevelopment in infants. This study investigates the impact of DCC on neonatal hemoglobin levels in term infants within Purwakarta Regency, Indonesia. An observational study was conducted on term infants born at two hospitals in Purwakarta Regency, Indonesia. One hospital routinely practiced immediate cord clamping (ICC, within 30 seconds), while the other practiced DCC (3 minutes after birth). Hemoglobin levels were measured within 24 hours of birth. A total of 200 infants (100 ICC, 100 DCC) were enrolled. The mean hemoglobin level in the DCC group was significantly higher than in the ICC group (17.5 g/dL vs. 16.2 g/dL, p < 0.001). Fewer infants in the DCC group required iron supplementation within the first six months (10% vs. 25%, p = 0.01). In conclusion, DCC is associated with higher hemoglobin levels in term infants in Purwakarta Regency, Indonesia. This practice may reduce the need for iron supplementation and improve early infant health outcomes.